Scandium as a pre-catalyst for the deoxygenative allylation of benzylic alcohols. Issue 1 (6th December 2017) - Šolić, Ivan; Seankongsuk, Pattarakiat; Loh, Joanna Kejun; Vilaivan, Tirayut; Bates, Roderick W.
Abstract : Scandium triflate is an effective pre-catalyst for the deoxygenative allylation of benzylic and benzyhydryl alcohols. Abstract : Scandium triflate is an effective pre-catalyst for the deoxygenative allylation of benzylic alcohols with a narrow substrate window. The reaction is shown to proceed through a "hidden Brønsted acid" mechanism. The reaction is efficient provided that the aryl group is neither too electron rich nor too electron poor. It is shown that this allows useful selectivity. The reaction also works for benzyhydryl alcohols with broader scope. The reaction may also be catalysed by Nafion.